Regulation of transcription of the Escherichia coli phosphoenolpyruvate carboxykinase locus: studies with pck-lacZ operon fusions. - Goldie, H (1984)
Mutants of Escherichia coli containing genetic fusions of lacZ to the pck (phosphoenolpyruvate carboxykinase) locus were isolated by using Mu d(lacZ Ampr) bacteriophage. Synthesis of beta-galactosidase in these strains is regulated by cyclic AMP and glucose (catabolite repression). Synthesis of beta-galactosidase by pck-lacZ fusions was induced in log-phase cells growing on gluconeogenic media, was repressed by glucose, and was also induced up to 100-fold at the onset of stationary phase in LB medium. This stationary-phase induction required cyclic AMP and some other unknown regulatory signal.